Estudo de impacto de vizinhança : Cuiabá - MT - Takeshima, Thabata Terumi (2018)
The central objective of the research is to analyze the urban instrument "Neighborhood Impact Study (EIV)" and "Neighborhood Impact Report (RIV)" and its applicability in the production and reproduction of the urban space in Cuiabá-MT. This instrument, present in federal and municipal laws, advocates the requirement of "participation" of society for its applicability, whose "participatory" procedure focuses on work to the detriment of the technical aspect that it also covers. For that, we discussed the legal aspects related to the social functions of the property and the city as objects and conditions of/for political dispute. This perspective was drawn from the understanding that the State, as a producer of urban space in the promulgation and mediation of these legal aspects, acts in a conflicting and contradictory way, but within the capitalist structural limits that condition its existence. As empirical data, the construction process of the legal aspect of the EIV-RIV in Cuiabá-MT was presented, some licensing processes (through EIV-RIV) of residential projects were analyzed, official documents such as the minutes of the "participatory" stages, the terms of commitment, the terms of conduct adjustment, among others. In this way, articulating the theoretical framework with the empirical data, it was analyzed how the EIV-RIV urbanization instrument materializes beyond the legal aspect in which it is beacon, besides making a critic in the way the Municipal Public Power conducts this process of licensing in Cuiabá-MT